MAKNA AGAMA DALAM STRUKTUR SOSIAL MASYARAKAT ADAT PAPUA - Natasya Virginia Leuwol; Leidy Damima; Zeth Momot; Bentelina Rut Fiay (Yayasan Nusantara Hasana Berdikari, 2024)
This study aims to analyze the meaning of religion within the social structure of Papuan indigenous communities. In this context, religion is not merely understood as a system of spiritual belief, but also as a social force that shapes values, norms, leadership, and social relations. This research employs a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews with indigenous leaders and religious figures, participatory observation of religious and customary activities, and document analysis. Data analysis was conducted using thematic analysis, and data validity was ensured through source and method triangulation. The findings indicate that religion plays a significant role in strengthening social solidarity, legitimizing customary leadership, and serving as a means of social conflict resolution. Furthermore, religion is integrated with local wisdom and contributes to the preservation of cultural sustainability within Papuan indigenous communities. This study affirms that the integration of religion and customary practices forms a distinctive, dynamic, and adaptive social structure in Papuan indigenous society.